2017
DOI: 10.3390/met7060196
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Texture and Phases in 3D Printed IN718 Alloy Subjected to Homogenization and HIP Treatments

Abstract: 3D printing results in anisotropy in the microstructure and mechanical properties. The focus of this study is to investigate the structure, texture and phase evolution of the as-printed and heat treated IN718 superalloy. Cylindrical specimens, printed by powder-bed additive manufacturing technique, were subjected to two post-treatments: homogenization (1100 • C, 1 h, furnace cooling) and hot isostatic pressing (HIP) (1160 • C, 100 MPa, 4 h, furnace cooling). The Selective laser melting (SLM) printed microstruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
84
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 193 publications
(98 citation statements)
references
References 47 publications
14
84
0
Order By: Relevance
“…found that post-manufacturing treatments reorganized the {002} dominant columnar grain structure into equiaxed grains with a {111} dominant orientation [13]. (Nb0.78Ti0.22)C carbides and δ-phase precipitates were also reported to form due to the diffusion of constituent elements and the high temperature treatment which led to dissolution of ′′ [13].…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…found that post-manufacturing treatments reorganized the {002} dominant columnar grain structure into equiaxed grains with a {111} dominant orientation [13]. (Nb0.78Ti0.22)C carbides and δ-phase precipitates were also reported to form due to the diffusion of constituent elements and the high temperature treatment which led to dissolution of ′′ [13].…”
Section: Methodsmentioning
confidence: 99%
“…(Nb0.78Ti0.22)C carbides and δ-phase precipitates were also reported to form due to the diffusion of constituent elements and the high temperature treatment which led to dissolution of ′′ [13].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations